Application of Compost Tea and Ascorbic Acid to Increase Productivity and Antioxidant Activity of The Common Bean (Phaseolus vulgaris L.) - Nasution, Ahmad Raihan; Dwiartama, Angga; Putra, Ramadhani Eka (School of Life Sciences and Technology, Institut Teknologi Bandung, 2024)
The common bean is a functional food rich in nutrients and bioactive compounds that support good health. Improving common bean yield is essential for enhancing nutrition within communities. This study examined the effects of compost tea, ascorbic acid, and their combination on the productivity and antioxidant activity of upright common beans. The experiment involved six treatments, including a control (water spraying) (P1), ascorbic acid (P2), manure compost tea (P3), BSF larvae production residue (BSFR) compost tea (P4), manure compost tea and ascorbic acid (P5), and BSFR compost tea and ascorbic acid (P6). All treatments, except P6, showed significant differences in productivity. P2 recorded the highest yield at 8,13 tons/ha/cycle and increased productivity by 19,03%, followed by P5 (9,22%) and P3 (3,95%) compared to P1 (control). P4 had a slight reduction in productivity by 3,95% than P1. A combination of compost tea and ascorbic acid increased productivity by 5,07% for P5 and 4,63% for P6 compared to the treatment without combination with ascorbic acid. P2 had the lowest IC50 value, 17,46 µg/ml, indicating the highest antioxidant activity. Compost tea and ascorbic acid combined reduced the IC50 value by 23,12% for P5, but P6 increased it by 32,59%. P5 improved the antioxidant activity of common bean pods when combined with compost tea and ascorbic acid, while P6 demonstrated a better effect without the combination. P3 and P6 had higher IC50 values than the control but lacked the potential to improve the antioxidant activity of common bean pods.